Household management participation of emerging adult children of families with separated couples - Alegre, Ma. Ines Regina D.; Dolor, Jyla C. (College of Home Economics, University of the Philippines Diliman, 2023)
This qualitative study looks into the household management participation of emerging adult children of families with separated couples, their motivations, challenges, and support needed. 10 male and 10 female participants, between the ages of 18 to 25 years old, and were staying in the residence of either parent located in the National Capital Region (NCR) were chosen through purposive sampling. In-depth interviews were used to gather data then analyzed through thematic analysis. Results showed that the emerging adult children have varied participation in the management of their households. Areas of household management participated in include, household chores, finances, decision-making, socio-emotional support, sibling support, and fulfillment of other parental roles. Their motivations in participating and the challenges they have encountered also vary greatly, which resulted from the need to restructure and reorganize the group, in order to adapt to the changes brought by their separated family setup alongside their unique experiences in the emerging adulthood stage. The support needed by these emerging adult children is primarily a result of their desire to adjust in the changes in the management of their households alongside navigating through adulthood. Overall, these emerging adult children participate in the management of their household in response to the system changes occurring within their family and to achieve equilibrium, aligned with the principles of Family Systems Theory of Klein and White.